Sector Specific News Shocks in Aggregate and Sectoral Fluctuations - Christoph Görtz; John D. Tsoukalas (Center for Economic Studies and ifo Institute (CESifo), 2013)
Using a two-sector estimated DSGE model with a financial channel we show the sector where TFP news arrives matters for its propagation and quantitative importance. Anticipated increases in TFP expected to arrive in the consumption sector are expansionary while those in the investment sector are broadly contractionary. Our results indicate a significant role of TFP news shocks as a predictive force behind fluctuations. Consumption sector TFP news shocks generate both aggregate and sectoral co-movement and account for approximately, 31%, 21%, 43%, 29% in the variance of output, investment, hours worked, and consumption respectively in business cycle frequencies. The financial channel provides amplification to TFP news. We discuss the relationship of our findings with VAR based estimates of TFP news shocks.
Keywords: E20; E30; 330; news; business cycles; DSGE; Bayesian estimation